Efficacy of Antenatal Intravenous Immunoglobulin Treatment in Pregnancies at High Risk due to Alloimmunization to Red Blood Cells - Mayer, Beate (Transfus Med Hemother, 2018)
BACKGROUND: Alloimmunization to red blood cells (RBCs) may result in fetal anemia prior to 20 weeks gestation. The question as to whether early commencement of antenatal treatment with high-dose intravenous immunoglobulins (IVIG) may prevent or at least delay the development of fetal anemia in the presence of alloantibodies to RBCs is highly relevant. PATIENTS AND RESULTS: Here we describe a patient with high-titer anti-K and two other severely affected pregnant women with a history of recurrent pregnancy loss due to high-titer anti-D or anti-D plus anti-C. Early commencement of treatment with IVIG (1 g/kg/week) resulted in prevention of intrauterine transfusion (IUT) in the former two cases, and in a significant delay of development of fetal anemia in the remaining case (26 weeks gestation). CONCLUSION: Based on our findings and of previously published cases, early initiation of treatment of severely alloimmunized women with IVIG (1 g/kg/week) could potentially improve the outcome of fetuses at risk.